Chalcone: A potential scaffold for NLRP3 inflammasome inhibitors - Pritam Thapa; Sunil P. Upadhyay; Vikas Singh; Varun C. Boinpelly; Jianping Zhou; David K. Johnson; Prajwal Gurung; Eung Seok Lee; Ram Sharma; Mukut Sharma (Elsevier, 2023)
Overactivated NLRP3 inflammasome has been shown to associate with an increasing number of disease conditions. Activation of the NLRP3 inflammasome results in caspase-1-catalyzed formation of active pro-inflammatory cytokines (IL-1β and IL-18) resulting in pyroptosis. The multi-protein composition of the NLRP3 inflammasome and its sensitivity to several damage-associated molecular patterns (DAMPs) and pathogen-associated molecular patterns (PAMPs) make this extensively studied inflammasome an attractive target to treat chronic conditions. However, none of the known NLRP3 inhibitors has been approved for clinical use. Sulfonylurea and covalent inhibitors with electrophilic warhead (Michael acceptor) are among the prominent classes of compounds explored for their NLRP3 inhibitory effects. Chalcone, a small molecule with α, β unsaturated carbonyl group (Michael acceptor), has also been studied as a promising scaffold for the development of NLRP3 inhibitors. Low molecular weight, easy to manipulate lipophilicity and cost-effectiveness have attracted many to use chalcone scaffold for drug development. In this review, we highlight chalcone derivatives with NLRP3 inflammasome inhibitory activities. Recent developments and potential new directions summarized here will, hopefully, serve as valuable perspectives for investigators including medicinal chemists and drug discovery researchers to utilize chalcone as a scaffold for developing novel NLRP3 inflammasome inhibitors.